Determinants of left atrioventricular coupling index: the multi-ethnic study of atherosclerosis (MESA). (3rd October 2022) - Pezel, T; Ambale Venkatesh, B; De Vasconcellos, H; Kato, Y; Post, W P; Wu, C; Heckbert, S; Bluemke, D; Cohen-Solal, A; Logeart, D; Henry, P; Lima, J
Abstract: Background: Recent studies have described a novel left atrioventricular coupling index (LACI), which had a better prognostic value than individual left atrial (LA) or left ventricular (LV) parameters measured separately to predict cardiovascular events. Purpose: To identify the determinants of the LACI and its 10-year annual change (ΔLACI), measured by cardiovascular magnetic resonance (CMR), and to better understand the parameters governing this left atrioventricular coupling. Methods: In the Multi-Ethnic Study of Atherosclerosis (MESA), 2, 112 study participants, free of cardiovascular disease at baseline, had LACI assessed by CMR imaging at baseline (LACIBaseline, 2000–2002) and 10 years later (2010–2012). The LACI was defined as the ratio of LA to LV end-diastolic volumes. Linear regression analyses were performed to identify independent determinants of LACIBaseline or ΔLACI. Results: In the 2, 112 participants (58.8±9.1 years, 46.6% male), after adjustment for all covariates, age was independently associated with both LACIBaseline (R2=0.10, slope=0.16) and ΔLACI (R2=0.15, slope=0.008, both p<0.001). African Americans had the highest LACIBaseline value (18.0±7.7%). Although there was no difference in LACIBaseline between women and men (p=0.19), ΔLACI was higher in women than in men (1.0±1.1 vs. 0.8±1.0%/year, p<0.001). Diabetes and a higher BMI were independently associated with LACIBaseline (both p<0.001). LACIBaseline was independently associated with LV myocardial fibrosis markers (native T1: R2=0.11, slope = 0.09, p=0.038; and extra-cellular volume: R2=0.08, slope = 0.28, p=0.035) and NT-proBNP levels (R2=0.10, slope = −1.11, p<0.001) but was not associated with IL-6 or hsCRP. Conclusions: Age, sex, ethnicity, diabetes, and BMI were independent determinants of LACI. LACI was independently associated with LV myocardial fibrosis markers and NT-proBNP levels. Funding Acknowledgement: Type of funding sources: None.